Factors Analysis And Profit Achievement For Trading Company By Using Rough Set Method - Sembiring, Muhammad Ardiansyah; Azhar, Zulfi (Universitas Dharma Wacana, 2017)
This research has been done to analysis the financial raport fortrading company and it is intimately related to some factors which determine the profit of company. The result of this reseach is showed about New Knowledge and perform of the rule. In discussion, by followed data mining process and using Rough Set method. Rough Set is to analyzed the performance of the result. This reseach will be assist to the manager of company with draw the intactandobjective. Rough set method is also to difined the rule of discovery process and started the formation about Decision System, Equivalence Class, Discernibility Matrix, Discernibility Matrix Modulo D, Reduction and General Rules. Rough set method is efective model about the performing analysis in the company. Keywords : Data Mining, General Rules, Profit,. Rough Set.